Perbedaan Prokrastinasi Akademik Ditinjau Dari Pola Asuh Orang Tua Pada Siswa Di SMK Negeri 1 Lubuk Pakam - Ema Rahmadiah; Annawati Dewi Purba (Jouska: Jurnal Ilmiah Psikologi, 2023)
This writing aims to see the differences in academic procrastination in terms of parenting patterns for students at SMK Negeri 1 Lubuk Pakam. The problem is focused on procrastination and parenting. In order to approach this problem, the theoretical reference from Ghuffron and Risnawati is used. The method of collecting data using the academic procrastination scale and screening on parenting patterns. The subjects in this study were students of SMK Negeri 1 Lubuk Pakam totaling 100 students. This research is analyzed quantitativ. data analysis method used in this study is the 1-way ANOVA analysis technique. the following results can be obtained, there are significant differences in academic procrastination in terms of permissive, authoritarian and democratic parenting in students at SMK Negeri 1 Lubuk Pakam.